Against D.H. Lawrence: St. Mawr, the nonhuman and the phantasms of reading. Issue 5 (4th May 2021) - Bostock, Camilla
ABSTRACT: This essay argues that the 'culture of redemption' which has developed around D.H. Lawrence's work tends to overshadow other, non-narrative forces of resistance at work in the Lawrencian idiom, ones that can help us to do the essential (but not essential ist ) work of thinking about nonhuman life today. I propose that a new (or perhaps, by now, old, passé) consideration of form, language and letters, is crucial for reading Lawrence, particularly his writing about nonhuman life. This essay seeks to challenge the existing, dominant readings of animality as ultimately soteriological in his oeuvre by embodying a mode of 'reading-against'. Such a reading would attend to that which is, in Jacques Derrida's terms, 'non(bio)degradable': hard to swallow, an uncanny indigestion .